2022
DOI: 10.1111/1744-7941.12360
|View full text |Cite
|
Sign up to set email alerts
|

Public healthcare in Pakistan: a people management solution?

Abstract: Pakistan is a developing country under severe pressure to provide efficient and effective healthcare to its population owing to inadequate financial and human resources and limited management capabilities. This study explores the role and practice of human resource management (HRM) in three Pakistani public teaching tertiary hospitals. We interviewed leaders and managers in these hospitals to gain a better understanding of the context, challenges and opportunities for HRM. Our thematic analysis revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Lack of resources, unfairness, accountability and poor governance are some of the additional obstacles to providing excellent healthcare in Pakistan (Faisal et al , 2022). Prior evaluations revealed that public and private hospitals had different patient capacities.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of resources, unfairness, accountability and poor governance are some of the additional obstacles to providing excellent healthcare in Pakistan (Faisal et al , 2022). Prior evaluations revealed that public and private hospitals had different patient capacities.…”
Section: Methodsmentioning
confidence: 99%
“…HPWS is based on specific coordinated HR practices that maximize employee commitment, knowledge, motivation, skills, and satisfaction and combat burnout and turnover (Bayo-Moriones & Galdón-Sánchez, 2010;Sun & Mamman, 2022). Bundles of HR practices work better than individual ones (e.g., Lin et al, 2020) and build a particular human capital of aggregate knowledge, skills, and abilities (Lepak et al, 2006;Lin et al, 2022) to encourage personal effort (e.g., Faisal et al, 2023). A thorough HPWS should be able to boost and reinforce employee ability, motivation, and opportunities (Lepak et al, 2006), and also employees benefit from meaningful performance, attitudes, and behaviors (cf.…”
Section: High-performance Work Systemsmentioning
confidence: 99%
“…First, we collected the data from the healthcare sector, specifically from major hospitals located in two provinces -Sindh and Punjab in Pakistan. Importantly, both these provinces are well known for their development, and major hospitals were selected because these hospitals have availability and accessibility of good quality healthcare services (Faisal et al 2022). Furthermore, these major hospitals are an established center of artificial intelligence and they are specialized in it by providing healthcare services to the people in Pakistan (Tribune 2021).…”
Section: Research Contextmentioning
confidence: 99%